2013
DOI: 10.1371/journal.pone.0081288
|View full text |Cite
|
Sign up to set email alerts
|

Breed-Specific Hematological Phenotypes in the Dog: A Natural Resource for the Genetic Dissection of Hematological Parameters in a Mammalian Species

Abstract: Remarkably little has been published on hematological phenotypes of the domestic dog, the most polymorphic species on the planet. Information on the signalment and complete blood cell count of all dogs with normal red and white blood cell parameters judged by existing reference intervals was extracted from a veterinary database. Normal hematological profiles were available for 6046 dogs, 5447 of which also had machine platelet concentrations within the reference interval. Seventy-five pure breeds plus a mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
48
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 46 publications
12
48
1
3
Order By: Relevance
“…Controlling for litter size, Boerboel and bull terrier bitches are expected to have 1.7% higher and German shepherd bitches 3.7% higher mean haematocrits before caesarean section than the mean (43.2%) of English bulldog bitches. Breed specific changes in haematological variables have been reported and related to genetic phenotypes [23]. Our data support this contention.…”
Section: Discussionsupporting
confidence: 87%
“…Controlling for litter size, Boerboel and bull terrier bitches are expected to have 1.7% higher and German shepherd bitches 3.7% higher mean haematocrits before caesarean section than the mean (43.2%) of English bulldog bitches. Breed specific changes in haematological variables have been reported and related to genetic phenotypes [23]. Our data support this contention.…”
Section: Discussionsupporting
confidence: 87%
“…) but with variation also between dog breeds (Lawrence et al . ). Most notable is the syndrome of macrothrombocytopaenia in cavalier King Charles spaniels and Akitas and the relative thrombocytopenia in greyhounds (Pedersen et al .…”
Section: Normal Platelet Anatomy and Physiologymentioning
confidence: 97%
“…Previous studies have shown that hematologic variables are influenced by geography . Alternatively, the differences could be attributed to the age of the animals as age is another factor that influences hematologic variables . Additionally, the different reference populations did not necessarily contain animals of the same breed or lactation status.…”
Section: Mean Values 95% Ris Median Absolute Deviations (Mad) Minimentioning
confidence: 99%